1882 Md. Laws 656, § 2 - (:unkn) unknown (My University, 1882)
Ch. 424 §1: Prohibited the manufacture, sale, barter, or giving away toy pistol cartridges
Keywords: TRANSFER, MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES